Estimation and its determinants of total productivity changes of Peru factors 1980 -2019 - Arroyo Yupanqui, Marco Antonio (2021)
There are several ways to explain a country's economic growth in both the long and medium term. One of the best approaches to this is Total Factor Productivity (TFP). In Peru, it has been observed that productivity has seen a sharp drop in recent years, leading to a major slowdown in economic growth and bringing it well below its potential level. Therefore, the main objective of the research focuses on the need to determine peru's TFP within the analysis period of 1980-2019. With this, it will be possible to find the determinants of economic growth for both the medium and long term. To achieve the objective, various correlation analyses will be carried out between economic growth, explained with the country's Gross Domestic Product (GDP), and important macroeconomic variables such as investment and consumption. Investment will be found to be the variable that will be correlated with GDP. Therefore, it will be concluded that the private sector will stand out from the rest of the sectors. Then, the promotion of investment should influence the rest of the sectors of the country such as consumption and external. On the other hand, it should be noted that public spending will not influence GDP. Finally, the TFP will demonstrate that the consumption of intermediate and final goods will be of great importance for the country's growth.